The Effect of Methylphenidate on The Consciousness Level of Intoxicated Patients; a Double-Blind Clinical Trial - Faraz Zandiyeh; Maral Ramezani; Mahdieh Abiyarghamsari; Shahin Shadnia; Babak Mostafazadeh; Peyman Erfan Talab Evini; Omid Mehrpour; Mitra Rahimi (Archives of Academic Emergency Medicine)
Introduction: Intoxication-related unconsciousness is a frequent and challenging condition in emergency medicine, where rapid interventions are critical to improve patient outcomes. This study aimed to evaluate the efficacy of methylphenidate in improving consciousness levels of intoxicated patients.